Influência da testosterona no crescimento e desenvolvimento craniofacial de ratos - Reis, Caio Luiz Bitencourt (2020)
The aim of this study was evaluating the testosterone suppression impact on craniofacial growth in rats. Thirty-six Wistar rats were included in this study. Orchiectomy (ORX) was performed in experimental group (n=8), while sham surgery was performed in control group (n=18) with 23 days old. The animals were allocated in 4 groups: an ORX group (n=9) and a sham group (n=9) euthanized with 45 days old and an ORX group (n=9) and a sham group (n=9) euthanized with 73 days old. Radiographic Lateral Cephalograms were performed on all animals with 23, 45 and 73 days old. Cephalometric measurements were obtained and compared with t-student and Mann-Whitney tests performed with GraphPad Prism software. The p<0,05 values were statistically different. After euthanasia of the groups, the mandibular condyle, the pre-maxillary suture and the middle palatal suture were processed for qualitative histological analysis of sagittal and frontal sections stained in Hematoxylin and Eosina and Picrosírius and Hematoxylin. The images were obtained using conventional light microscopy and polarized light. Body weight was lower in ORX groups. Verticals and horizontals cephalometric measurements were lower in ORX groups. Cephalometric angles were also statistically different in ORX groups. Histological analyzes demonstrate a reduction in the differentiation of chondroblast precursor cells in the mandibular condyle in orchiectomized animals, in addition to the lower proliferation of osteoblasts and formation of bone trabeculae. There is a higher concentration of collagen fibers in the Sham groups compared to the ORX groups in the mandibular condyle, and type III collagen fibers were observed only in the Sham groups. In the median palatine suture, greater proliferation of osteoblast precursor cells was observed in animals of the control group. Type III collagen fibers were also observed only in the Sham groups. There were no significant differences in the premaxillary suture. Concludes that the testosterone suppression decreases the craniofacial growth during puberty of rats